Perkembangan Jumlah Fasilitas dan Pengunjung Objek Wisata di Kecamatan Rancabali, Kabupaten Bandung - Muhammad Akbar Pratama; Lia Warlina (Majalah Ilmiah UNIKOM, 2022)
Rancabali district in Bandung Regency Spatial Plan is included in the fourth hierarchical area chosen as a tourist center. Rancabali District has natural beauty, Sundanese traditional culture, and public education tours. The development of tourism in the Rancabali District has been apparent for five years between 2013 and 2018. This study aims to identify tourism developments based on the development of facilities for each tourist object, management of tourism objects, and visitor growth rate in the Rancabali District. The research method uses descriptive qualitative and interviews with tourism object managers. The development observed is the condition of tourist attractions for five years in the Rancabali District. Within five years, there were three new tourist attractions from 13 attractions in Rancabali District; there were developments in facilities in each tourist attraction, including 18 new inns, five new bathing pools, three cafes, and one outbound. The management of tourist objects in the Rancabali District varies the length of time they are managed. The longest is in the Situ Patenggang tourist attraction, which has rented the land area for 42 years. The growth rate of visitors illustrates tourism development in the Rancabali District; the most significant growth rate is in new tourist objects Glamping Lakeside which has an average growth of 47% over three years. The identification of tourism development in the Rancabali shows four forms of development, i.e., the existence of three new tourist objects, increasing the number of facilities in each tourist attraction, managing each different tourist attraction, and the number of visitor growth rates. Key Words : Rancabali District, tourism facilities, tourism management, tourism object